[Book review] Andreas Schmidt & Daniela Hahn (eds.), Unwanted - Johansson, Karl G. (Journal of Northern Studies, 2024)
Review of: Andreas Schmidt & Daniela Hahn (eds.), Unwanted. Neglected Approaches, Characters, and Texts in Old Norse-Icelandic Saga Studies, München: Utzverlag 2021